TEKNIK PENCIPTAAN ASOSIASI PORNOGRAFI DALAM WACANA HUMOR BAHASA INDONESIA - Tommi Yuniawan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This study describes the techniques of creating pornographic association in Indonesian humorous texts. The data were Indonesian humorous texts which have pornographic association and their contexts. The texts were selected randomly based on these considerations: (1) the texts are Indonesian ones, (2) the texts represent the use of Indonesian language at present, and (3) the texts contain pornographic association. The data analysis was done through two procedures. They are: (1) the analysis during the process of collecting the data, and (2) the analysis after collecting the data. Then, in order to get the appropriate interpretation, these steps were followed by: (1) discussion, (2) repeated checking, and (3) consultation. Based on the analysis of the data, it can be concluded that the techniques of creating pornographic association in Indonesian humorous texts involve: (1) double meaning technique, (2) metaphor technique, (3) guessing technique, and (4) eufemism technique.